Exchange Rate Policy in Morocco and Persistence of Real Exchange Rate Misalignments - Bouzahzah, Mohamed; BACHAR, Radouane (International Journal of Economics and Financial Issues, 2013)
In this paper, we measure, using Moroccan data, the misalignment of the real exchange rate of the Dirham, based on estimates in respect of the period from 1980 to 2012, a long term relationship between the real exchange rate and its fundamentals: namely terms of trade, trade policy, the growth rate of real GDP, Gross Fixed Capital Formation, the flow of foreign capital and government spending. The objective of this article is to highlight the persistent nature of misalignments of the real exchange rate of the Dirham, especially since the adoption by Morocco of a policy exchange rate based on the attachment of the Dirham to a basket of currency and fixing the nominal exchange rate by the monetary authorities. The econometric estimations show that persistent misalignments may find its explanation in the structural characteristics of the Moroccan economy represented by the fundamental variables used in the estimated model (productivity, investment, trade policy, etc.). Keywords: equilibrium real exchange rate; misalignment; cointegration; persistence. JEL Classifications: C13; C32; F31